Avaliação do conhecimento dos pacientes oncológicos sobre seu diagnóstico, tratamento e prognóstico - Guedes, Lara Regina Aguiar (2017)
The doctor-patient communication does not end with the disclosure of the diagnosis, it extends to the discussion of therapeutic planning and prognosis. However, due to the association of cancer diagnosis to death and suffering, and despite the patient’s right to know it, there are barriers to the disclosure of such information. Objective: investigate the patients’ awareness of their diagnosis, treatment and prognosis in the Clinical Oncology sector of the Hospital de Base in São José do Rio Preto (HB). Method: 87 patients were interviewed between the second and third appointment of the clinical Oncology service. The second appointment was with the third-year residents of the medical residence program in Clinical Oncology. Two standardized instruments, the Hospital Anxiety and Depression Scale and the Questionnaire applied to cancer patients were used; as well as sociodemographic data and information about the service of the multi-professional team. Results: The participants were mostly men (71%), average age of 60; low level of education (illiterates 11,5% and 55,2% hasn’t completed middle school); diagnosed with colorectal cancer (26,4%), oral cavity (C00- C10, 12,6%) and lung (9,2%); clinical staging IV (49,4%); exclusive or combined chemotherapy treatment (94,2%); didn’t report any difficulty in understanding the disclosure of the diagnosis (91,9%) nor treatment (87,4%); felt capable (86,2%) and free (85%) to decide on the treatment; aware of the evolution of the disease (67,8%); wanted to obtain all the information about their disease (74,7%) and presented unlikely scores to anxiety and/or depression (74,7%). Conclusions: According to the results, the participants knew about their disease, treatment and prognosis, and presented low rates to anxiety and depression symptoms.